The export effects of inward Foreign Direct Investment in the South African economy - Matlasedi, N. T.; Ncanywa, T. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
It is an open secret that the world was plunged into a world financial crisis caused by the United States credit bubble in the mid-late 2000’s. During this time, South Africa was not spared the negative effects of this crisis. It was also during this time that South Africa’s level of exports and inflows of foreign direct investment declined sharply. Thus, it is against this backdrop that the study investigates the relationship between exports and foreign direct investment inflows in the South African economy seeing that they seem to be moving in the same direction. Using yearly secondary data spanning the period 1980 – 2015, the Johansen cointegration test was employed to test for the long run cointegrating relationship between the variables in the export model. The Granger causality test was employed to test for the direction of causality between the variables whereas the Vector Error Correction Model (VECM) was employed to estimate the speed of adjustment. The results from the cointegration test showed that there is a long run relationship between exports, real economic growth, inward FDI and real effective exchange rate. There is also a one-way causal relationship running from exports to inward FDI. The long run export model shows that an increase in FDI induces an increase in exports. The paper recommends the strengthening of trade policy in the way of providing export subsidies to domestic producers in order to help lower their prices and be able to compete in international markets. As a more reliable instrument to increase exports, the government should adopt exchange rate policy to stabilise the exchange rate.
Journal article, Published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017
Keywords: Exports; Foreign direct investment; Real GDP; Real Effective Exchange Rate; Investments, Foreign; Export controls; Foreign trade regulation -- South Africa